Custos no transporte escolar: um estudo na prefeitura municipal de Nova Boa Vista RS comparação entre terceirização e transporte com frota própria no transporte escolar? - Borella, Andressa (2023)
"The education guaranteed by the Federal Constitution aims at the valorization of public education and the enhancement of citizenship. To enable access to education, school transportation becomes necessary for the commute of students residing in rural areas to schools located in urban areas. This study aims to analyze the cost between the hiring of Outsourced and Owned School Transportation in the municipal government of Nova Boa Vista/RS. The methodology used was descriptive, qualitative research, a case study where data were collected directly from the Municipal Government through financial statements, mileage records, among others. The study was conducted from 01/01/2022 to 06/31/2023, where it was possible to identify all costs related to school transportation for both the owned fleet and the outsourced one, as well as the number of students and kilometers traveled per day for each transporter. From the collected data, tables were created comparing each modality, which revealed that the outsourced transportation carried more students than the owned one in both analyzed periods. Regarding mileage, the outsourced transportation covered more kilometers in both analyzed periods. As for the cost per kilometer traveled, the owned transportation cost less in both periods analyzed in 2022, being 0.635 cents, and in the first semester of 2023, it was 0.975 cents. Thus, it can be concluded that transportation with its own fleet cost less to the public coffers both in 2022 and in the first six months of 2023.